Volunteering at the Olympic and Youth Olympic Games: More Than a Distant Memory?. Issue 1 (2nd January 2023) - Wang, Yan; Derom, Inge; Theeboom, Marc
Abstract: In recent years, cities have shown an interest in using the hosting of sport mega-events as a leverageable resource in realizing long-term impacts for individual volunteers. However, previous research has provided limited evidence of the realization of anticipated impacts in the post-event period. This study focuses on the long-term impacts of Olympic and Youth Olympic volunteering in terms of memory, attitudes, and behaviors. Data were collected from a sample of 353 volunteers who have been involved with the 2008 Beijing Olympic and Paralympic Games, the 2010 Singapore Youth Olympic Games, and the 2014 Nanjing Youth Olympic Games. Results show that volunteers can easily access their Olympic and Youth Olympic memory, with vivid, emotional, and visual details, while the overall tone of their volunteer memory is positive over a long period. Volunteering at the Olympic and Youth Olympic Games can be understood as a positive life-changing event and participants have reported high scores on the attitudes in terms of the interest in the Olympic Movement. Findings reveal that the sharing of the memory by volunteers and the time perspective have been found to contribute significantly to broader impacts in terms of attitudes about the Olympic Movement and subsequent volunteer behaviors. Implications for sport mega-event volunteer management are discussed.